Role of Zinc Homeostasis in the Pathogenesis of Diabetic Osteoporosis in Mice - Yoshinori Mizuno; Fuka Takeuchi; Marina Morimoto; Yukinori Tamura (Diabetology)
Background: Diabetes induces osteoporosis primarily by impairing osteoblast function. Intracellular zinc homeostasis, which is controlled by zinc transporters, plays a significant role in osteoblast differentiation. In the present study, we aimed to explore the role of zinc homeostasis in the pathogenesis of diabetic bone loss using a diabetic mouse model. Methods: Streptozotocin (STZ)-induced diabetic female mice were used for in vivo experiments. In vitro, the effects of zinc transporter knockdown using small interfering RNA was investigated in MC3T3E1 pre-osteoblastic cells. Results: STZ-induced diabetic mice exhibited severe bone loss and decreased expression of osteogenic genes, as well as a decrease in zinc content and the expression of several zinc transporters localized in the cellular membrane, including Zip6, Zip9, and Zip10 in the tibia. Moreover, the messenger RNA (mRNA) levels of Zip6, Zip9, and Zip10 were positively correlated with trabecular bone mineral density in the tibiae of diabetic mice. This in vitro study, using MC3T3E1 pre-osteoblastic cells, revealed that knockdown of Zip6 reduced the expression of osteogenic genes in pre-osteoblastic cells. Additionally, Zip6 knockdown downregulated protein levels of phosphorylated p38 mitogen-activated protein kinase (p38MAPK) in pre-osteoblastic cells, and this change was observed in the tibiae of diabetic mice. Conclusions: Our data suggest that the downregulation of zinc transporters localized in the cellular membrane, such as Zip6, may be involved in the impairment of osteoblastic differentiation through the inhibition of p38 MAPK signaling, leading to osteoporosis under diabetic conditions. Maintaining zinc homeostasis in bone tissues may be vital for preventing and treating diabetic bone loss, and zinc transporters may serve as novel therapeutic targets for diabetic osteoporosis.